Determination of Safe Return to Play for Athletes Recovering from Infectious Mononucleosis: A Review of the Literature - Waninger, K. N.; Harcke, H. T. (Clinical Journal of Sport Medicine, 2005)
Abstract: Objective: Infectious mononucleosis is an acute self-limited disorder diagnosed by clinical and hematologic measures. This paper reviews the literature regarding the decision-making process for return to play in individuals at risk for complications due to infectious mononucleosis.